Indian Guides Pow Wow at YMCA Camp at Sequoia Lake - Watkins, Howard::::::::: (1986)
Josiah Gordon, Jared Gordon and Adam Watkins swimming in dock area at Sequoia Lake Shows U-shaped wood-plank dock with lifeguard station on far corner